Engineering Properties and Production Costs of Paving Blocks Incorporating Different Types of Agricultural Wastes - Prayuda, Hakas; Monika, Fanny; Cahyati, Martyana Dwi; Nurega, Bagus Arya; Fathurrahman, M; Subani, Achmad Yusuf Firman Hidayat (International Journal of Sustainable Construction Engineering and Technology, 2025)
Open-field burning is still widely utilized as a traditional waste disposal method in agriculture, particularly in developing countries. In some locations in Yogyakarta, Indonesia, the ashes formed by the open field burning of agricultural waste have not been utilized to their full potential. This research aims to utilize waste ashes from three different agricultural industries, including rice husk ash (RHA), sugarcane bagasse ash (SBA), and corn cob ash (CCA), as cement replacements in the manufacture of paving blocks. The purpose of utilizing agricultural waste ashes was to reduce soil pollution caused by waste in plantation areas around Yogyakarta, as well as initiatives to reduce the use of cement for non-structural constructions. The laboratory scale experiments examined the engineering properties of paving blocks, including slump flow, compressive strength, splitting tensile strength, flexural strength, mass density, mass loss, water absorption, porosity, and initial suction rate (IRS). The fresh properties experiment was done during the mixing process when the mortar was in the fresh state, the mechanical properties experiment was done during the curing period of 7, 14, and 28 days, while the physical properties experiment was only done on specimens after 28 days Besides, an analysis of the production cost was also conducted. This research found that the maximum amount of waste that can be used is 20% of the total binder for a composition ratio of 1:9 (binder: sand). The utilization of more than 20% of waste causes a significant decrease in fresh properties, prohibiting its rapid production and delaying the hardening process. Based on the mechanical properties, it was found that a 10% composition of agricultural waste ashes is the optimum amount recommended for use with comparable properties to normal paving blocks. In addition, by utilizing 10% of waste ashes in total binder, it is possible to reduce production costs by 2.25% to 2.43%.